Creation of Subject Identity in the Context of Sense Category in Pedagogy - Michalski, Jarosław (Paedagogia Christiana, 2014)
Culture provides some philosophical concepts composing fundaments of fair life, suggests solutions to key existential problems, defines social mechanisms for their maintenance. They compose a reference system of social and individual life. The type of social order in which human existence finds its course plays a crucial role in the process of development of own life and identity as it encompasses a framework of context for understanding the world and functioning in it, however always via finding the sense of life. The content of the presentation shall include application of sense category to the pedagogy and an attempt to answer the question: how to liven up the issue of development of sense of life in social life, upbringing, education, pedagogical way of thinking and how to help others to enter the path which would not lead to nothingness but to the plenitude of life and existence.